2022
DOI: 10.7759/cureus.28619
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Severity of Acute Appendicitis in Children Using Neutrophil-to-Lymphocyte Ratio (NLR) and Platelet-to-Lymphocyte Ratio (PLR)

Abstract: The ability to predict risk of perforation in acute appendicitis (AA) could direct timely management and reduce morbidity. Platelet-to-lymphocyte ratio (PLR) and neutrophil-to-lymphocyte ratio (NLR) are surrogate severity markers in infections. This study investigates the use of PLR and NLR as a marker for distinguishing uncomplicated (UA) and complicated appendicitis (CA) in children. Materials and methodsThis retrospective single-center study collected data between January 1, 2014, and December 31, 2020. Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 25 publications
0
4
0
2
Order By: Relevance
“…In complicated appendicitis, using neutrophil-to-lymphocyte ratio and PLR, the AUC and cut-off were 0.776 and 8.86, respectively. Meanwhile, in the current study, the results agree with those found in the previous study (shown in Table 3), in which a significant association was seen between NLR and the occurrence of complications (p-value = 0.00001) [14].…”
Section: Discussionsupporting
confidence: 93%
“…In complicated appendicitis, using neutrophil-to-lymphocyte ratio and PLR, the AUC and cut-off were 0.776 and 8.86, respectively. Meanwhile, in the current study, the results agree with those found in the previous study (shown in Table 3), in which a significant association was seen between NLR and the occurrence of complications (p-value = 0.00001) [14].…”
Section: Discussionsupporting
confidence: 93%
“…A retrospective single-center study assessed the use of NLR and PLR in predicting the severity of acute appendicitis in children, and their statistical analysis demonstrated both factors as independent predictors of complicated appendicitis. Using NLR and PLR AUC and cut-off was 0.776, 8.86 with a 95% CI of 0.730–0.822 and 0.694, 193.67 with a 95% CI of 0.634–0.755, respectively [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous scoring systems have been proposed in order to support the clinician in diagnosing and categorizing acute appendicitis, such as the Alvarado score, pediatric appendicitis score (PAS), the appendicitis inflammatory response (AIR), and Shera score. These scoring systems lack the sensitivity and specificity to anticipate the severity of acute appendicitis; thus, their use is not recommended by the WSES [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ayeni y colaboradores (6) respaldan el uso de la proporción de neutrófilos a linfocitos (NLR) y la proporción de plaquetas a linfocitos (PLR) para estratificar el riesgo de niños con apendicitis confirmada en entornos de recursos económicos limitados o donde no se encuentren los exámenes diagnósticos necesarios. Para el NLR, hallaron una sensibilidad del 70,3% y una especificidad del 70% con valor predictivo positivo (VPP) del 84,6% y un valor predictivo negativo (VPN) del 50,2%, y para el PLR, una sensibilidad del 64% y una especificidad del 61% con un VPP del 79,3% y un VPN del 42%.…”
unclassified